Analyzing Grammatical Errors to Improve English Writing Among Thai High School Students’ Interlanguage and Vocabulary Use - Matwangsaeng, Rangsawoot; Matwangsaeng, Pennapa; Sukying, Apisak; Min, Changyong (Theory and practice in language studies, 2025)
This study examines the grammatical errors and vocabulary types in the writings of Thai high school EFL students. Employing Dulay et al.’s (1982) surface strategy taxonomy, errors were categorized into omission, misformation, addition, and misordering to identify predominant error patterns. Additionally, the study assessed the vocabulary range via the General Service List and the Academic Word List. Findings indicated a significant reliance on high-frequency words and less frequent use of AWL vocabulary, stressing gaps in readiness for academic study. The study highlights the diagnostic value of error analysis in revealing insights into learners’ interlanguage development, reflecting their evolving understanding and hypothesis testing about the target language influenced by their first language. Grammatical errors, such as incorrect use of singular and plural forms, articles, and tense inconsistencies, were common, suggesting learners face structural and syntactic challenges. Omission errors emerged as the most prevalent, followed by misformation, addition, and misordering, indicating areas needing focused grammatical instruction. Vocabulary analysis revealed an 82.30% overlap of the first 1,000 GSL words in students’ texts, contrasting with the minimal use of AWL words, essential for academic success. The findings advocate for enhanced instructional strategies integrating GSL and AWL vocabularies and emphasizing systematic grammatical error correction to improve language proficiency and academic readiness. Future research should include more diverse learner populations and a broader range of error types to provide insights into language acquisition challenges and solutions. This study contributes to refining teaching methodologies and curriculum development to better prepare students for future academic challenges.